2014
DOI: 10.7906/indecs.12.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Cognitive Efficiency, Cognitive Ability and Motivation

Abstract: The current body of research often focuses on the problem of cognitive decline through ageing. People adapt to these changes of cognitive resources by using brain reserve. An overview of results of different studies on how cognitive abilities of older adults decline highlights high variability of conclusions and sometimes contradiction but it has been shown older adults can be as good as or even better than younger participants in specific domains. Among others, personal meaningfulness of a situation and close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Several other factors, such as age and education, can affect comprehension of figurative forms as well as cognitive performance in general 112 . A recent study 122 on proverb comprehension in a healthy population reported that subjective meaningfulness and closeness with the researcher can modulate test performance. Forty‐eight participants were divided into two age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Several other factors, such as age and education, can affect comprehension of figurative forms as well as cognitive performance in general 112 . A recent study 122 on proverb comprehension in a healthy population reported that subjective meaningfulness and closeness with the researcher can modulate test performance. Forty‐eight participants were divided into two age groups.…”
Section: Discussionmentioning
confidence: 99%
“…To develop more sensitive tests of figurative language that could be useful in disentangling typical cognitive aging from preclinical AD, one would need to go beyond frequency, abstractness, and syntactic complexity of these expressions and consider their internal features, as illustrated above by the example from semantic classes of proverbs. Perhaps such tests would challenge recent findings that cognitively healthy elderly people comprehend proverbs as well as young people in certain circumstances, 9 or even better, despite significant atrophy in the relevant brain areas. 10 Whether tests of figurative language will in the future have more clinical applicability in early diagnosis and monitoring of cognitive decline in dementia depends critically on improving their sensitivity, which in the case of proverb tests means taking into consideration their internal features, such as semantic class.…”
mentioning
confidence: 98%